Micropropagaçãode pitaia com ênfase em diferentes densidades de fluxo de fótons e organogênese indireta - Rodrigues, Mariane Aparecida (2017)
The cultivation of pitaya has been promising generating a search for new cultivation techniques. So the objective of this research was to promote a micropropagation protocol with a focus on the multiplication stage of pitayas (Hylocereus undatus) by indirect organogenesis and by means of different photon flux densities. Seedlings were previously germinated in vitro and provided explants for the two experiments. Organogenesis was obtained by means of identified seedlings and portions of apical and median explants under different growth regulators (TDZ and 2,4-D) and their concentrations 2,4-D: 2,0 and 4,0 mg L -1 ; TDZ: 2,0 and 4,0 mg L -1 and combinations with 2,0 mg L -1 of TDZ with 4,0 mg L -1 of 2,4-D and 2,0 of 2,4-D mg L -1 with an addition of 4,0 mg L -1 of TDZ and a control treatment, with three repetitions containing three ICS bottles, in an incomplete factorial. The percentage of callus coverage was evaluated at 45 and 60 days. After 60 days the most phenologically discrepant treatments (control, 2 and 4.0 mg of TDZ and 4.0 mg L -1 of 2,4-D) were followed for analysis by flow cytometry and scanning electron microscopy. In order to study the different photon flux densities, five photon flux densities (20,0; 57,0; 78,0;102,0 and 139,0 μmol m -2 .s -1 ) were used with five replicants (4 tubes / replicate) arranged in DIC.After 45 days the parameters were evaluated: cladodium length, half - height cladodium width, number of shoots and root, main root length and shoot dry matter, and the plants were submitted to anatomical and photosynthetic pigment analyses. It can be concluded that micropropagation by indirect organogenesis can be used for pitaya and that the growth regulators TDZ at the concentration of 2.00 mg L -1 is the most suitable for this function, as evidenced by the presence of characteristic structures demonstrated by scanning electron microscopy as conducting vessels and for generating genetically stable plants. It was also concluded that the luminous intensity of 102,0 μmol m -2 .s -1 is shown to be the most suitable for the cultivation of the species generating good growth, as well, it provides plants with anatomical characteristics and with a satisfactory amount of pigments.